Effects of knee position on the reliability and production of maximal and rapid strength characteristics during an isometric squat test - Palmer, T. B.; Pineda, J. G.; Durham, R. M. (Journal of Applied Biomechanics, 2018)
This study aimed to examine the effects of knee position on the reliability and production of peak force (PF) and rate of force development (RFD) characteristics during an isometric squat. Fourteen resistance-trained females performed isometric squats at 90, 120, and 150° knee angles (corresponding to parallel, half, and quarter squat positions, respectively) on 2 different occasions, from which PF, peak RFD, and early (RFD30, RFD50, RFD100) and late (RFD200) phase RFD variables were extracted. PF and RFD200 were highly consistent across trials for all 3 squat positions, with intraclass correlation coefficients (ICCs) ranging between 0.812-0.904 and coefficients of variation (CVs) between 6.6-19.4%. For peak and early RFD characteristics, higher ICCs and lower CV values were observed for the quarter squat (ICCs=0.818-0.852, CVs=17.3-19.4%) compared to the parallel (ICCs=0.591-0.649, CVs=30.1-55.9%) and half squats (ICCs=0.547-0.598,CVs=31.1-34.2%). In addition, isometric PF and RFD200 increased (P=.001-0.04) with squat position (parallel<half<quarter); however, there were no differences for peak RFD (P=.27), RFD30 (P=.99), RFD50 (P=.99), and RFD100 (P=.09). These findings suggest that performing isometric squats at higher (150°) rather than lower knee joint angles (90-120°) may provide for an improved capacity to produce greater PF and RFD200 as well as a more reliable testing position for measuring peak and early RFD characteristics.